1986
DOI: 10.1073/pnas.83.13.4918
|View full text |Cite
|
Sign up to set email alerts
|

Design of potent, orally effective, nonpeptidal antagonists of the peptide hormone cholecystokinin.

Abstract: We describe the design and synthesis of nonpeptidal antagonists of the peptide hormone cholecystokinin. Several of these compounds have high specificity and nanomolar binding affinity and are active after oral administration. To our knowledge, the design of such agents has not previously been accomplished for any peptide hormone. The structural similarities between these synthetic compounds and the anxiolytic 1,4-benzodiazepines are noted, and the potential of this structural feature for future design of ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
1
4

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(98 citation statements)
references
References 35 publications
0
93
1
4
Order By: Relevance
“…The effect of this CCKB/gastrin antagonist was relatively weak compared to PD 136450, whilst the selective CCKA antagonist devazepide was inactive at up to 300pumolkg-1 against the three stimulants. This latter observation is in keeping with the low affinity of devazepide for both the gastrin, and brain CCKB receptors (Chang & Lotti, 1986;Evans et al, 1986). However, our results with devazepide are in conflict with those in a similar study by Hirst et al (1991).…”
Section: Stimulation Ofgastric Acid Secretioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The effect of this CCKB/gastrin antagonist was relatively weak compared to PD 136450, whilst the selective CCKA antagonist devazepide was inactive at up to 300pumolkg-1 against the three stimulants. This latter observation is in keeping with the low affinity of devazepide for both the gastrin, and brain CCKB receptors (Chang & Lotti, 1986;Evans et al, 1986). However, our results with devazepide are in conflict with those in a similar study by Hirst et al (1991).…”
Section: Stimulation Ofgastric Acid Secretioncontrasting
confidence: 56%
“…However, neither the specificity nor the affinity of proglumide has been sufficient to permit its use in vivo to define the role of gastrin in the regulation of gastric acid secretion. In recent years other CCK receptor antagonists from several chemical classes have been developed, and although there are now available such benzodiazepines as devazepide 718 Chang & Lotti, 1986;Evans et al, 1986) with high affinity and high selectivity 'Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…9D) confirmed that L364,718 and L365,260 were not only CCK receptor antagonists but also behaved as specific and direct p38 MAP kinase inhibitors. L364,718 is a specific CCK1 receptor antagonist (45), whereas L365,260 is a specific CCK2 receptor antagonist, and both interact with p38 MAP kinase. SB202190 and SB203580 interact specifically with the CCK1 receptor but not with the CCK2 receptor.…”
Section: P38 Mapk Inhibitor and Cck Receptor Antagonist Interactionsmentioning
confidence: 99%
“…The cells achieve 10-fold increase in number in -12 days in serum-free medium (Inset). Both antagonists inhibited growth in a dose-dependent manner; half-maximal effect was seen with 24 ,uM (17,(34)(35)(36), but designing antagonists remains problematic. Unexpectedly, the substance P antagonist peptide A, which has minimal structural homology with bombesin, was found to be an antagonist for bombesin-stimulated enzyme secretion from dispersed pancreatic acini (17) and to block its growth-stimulatory effects (3,18).…”
Section: Peptide a And Peptide D Inhibit The Growth Of Sclc Cellmentioning
confidence: 99%